Data Mining as Support for Customer Relationship Management: A Case Study - dos Santos, José Gonalo (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This article describes the data mining application to CRM - Customer Relationship Management. The article starts with an introduction showing the importance of the CRM strategy for the company, after it’s introduced the theoretical about CRM, Knowledge Discovery Database and its stages, with emphasis to the mining stage and concludes with presentation of a case study and the conclusions. For the case study it was developed a prototype of an information system of a bookstore, it was implemented, beyond the conventional functions, the association rules discovery algorithm. The implementation of the data mining technique allowed to the system supply support so that the user knows better the client, becoming possible the application of the strategy of CRM.